Acoustic properties of multilayer sound absorbers with a 3D printed micro-perforated panel. (June 2017) - Liu, Zhengqing; Zhan, Jiaxing; Fard, Mohammad; Davy, John Laurence
Highlights: Micro-perforated panel absorbers (MPPA) are fabricated using 3D printing technology. Acoustic properties of composite MPPA layers are measured by using impedance tube method. The measured sound absorption coefficient results are theoretically validated. Acoustic properties variations with perforation ratio and depth of air cavity are discussed. The results obtained in this paper provided a new approach for the fabrication of composite sound-absorbing structures. Abstract: This paper investigates the acoustic absorption capability of a multilayer micro-perforated panel absorber (MPPA) whose front layer is produced by additive manufacturing. The MPPA layers are printed using a polymer material, where the different hole spacing is used to create different perforation ratios. The sound absorption coefficients are experimentally measured by using an impedance tube test, to investigate the effects of the perforation ratio and the depth of an airgap behind the MPPA. Also, a porous sound absorbing material layer is attached behind the MPPA layer in order to produce a multilayer acoustic absorber. The measurement results are compared to a theoretical approach. The comparisons show that the measured sound absorption coefficients agree fairly well with the theoretical model. The use of a porous sound absorbing material behind the MPPA broadens the frequency bandwith of the multilayer acoustic absorber. The frequency of the maximum sound absorption coefficient can be varied, by altering the perforation ratio of the MPPA and/or the depth of the airgap behind the panel.